Crystallin Alpha-B Overexpression as a Possible Marker of Reactive Astrogliosis in Human Cerebral Contusions - Becerra-Hernández, Lina Vanessa; Escobar-Betancourt, Martha Isabel; Pimienta-Jiménez, Hernán José; Buriticá, Efraín (Frontiers in Cellular Neuroscience, 2022)
The pathophysiology of traumatic brain injury (TBI) has not yet fully elucidated. Crystallin alpha-B (CRYAB) is a molecular chaperone that apparently tries to stabilize the rapid thickening of the intermediate filaments of glial fibrillary acidic protein (GFAP) during the process of reactive astrogliosis in response to TBI. Previous analyses of the gene expression profile in human brain contusion tissue showed us an exacerbated CRYAB overexpression. Here, we used DAB-immunohistochemistry and immunofluorescence to verify CRYAB overexpression, and to describe its expression and distribution in samples of contused cortical tissue derived from emergency decompressive surgery after severe TBI. The histological expression of CRYAB was mainly seen in subcortical white matter astrocytes of injured tissue. Most of the cells that overexpressed GFAP in the analyzed tissue also overexpressed CRYAB, a finding corroborated by the co-localization of the two markers. The only difference was the presence of a few pyramidal neurons that expressed CRYAB in layer V of the cerebral cortex. The selective vulnerability of layer V of the cerebral cortex during TBI could explain the expression of CRYAB in neurons of this cortical layer. Our results indicate a parallel behavior in the cellular expression of CRYAB and GFAP during the subacute response to TBI. These results lead us to postulate CRYAB as a possible marker of reactive astrogliosis in contused cortical tissue.